2019
DOI: 10.35808/ersj/1431
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of Paternalistic Leadership: Employee Discrimination and Nepotism

Abstract: Purpose: Paternalistic leadership is a prevailing leadership style in environments characterized by high power distance, collectivism, and uncertainty avoidance and is a general aspect of family businesses. With this in mind, the purpose of this study is to investigate paternalistic leadership in Turkish business environment and test the relationship between paternalistic leadership and employee discrimination and nepotism. Design/Methodology/Approach: Data were collected by a questionnaire from 183 employees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…This demand turns from the leaders of the employees to the expectation of creating a family atmosphere in the workplace. However, not being careful in the distribution of authority and benevolence may reveal employment discrimination arguments (Erden & Okten, 2019). Consequently, these arguments may bring hostility towards foreign workers because social, political, economic, and individual origins of xenophobia are intertwined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This demand turns from the leaders of the employees to the expectation of creating a family atmosphere in the workplace. However, not being careful in the distribution of authority and benevolence may reveal employment discrimination arguments (Erden & Okten, 2019). Consequently, these arguments may bring hostility towards foreign workers because social, political, economic, and individual origins of xenophobia are intertwined.…”
Section: Resultsmentioning
confidence: 99%
“…According to some studies authoritarian is negatively related to job performance and organizational citizenship behavior (Aryee, Chen, Sun, & Debrah, 2007;Liang, Ling, & Hsieh, 2007), job satisfaction and psychological well-being (Chao & Kao, 2005). Likewise, workplaces where the authoritarian paternalistic leaders are in charge create unpleasant work outcomes, feelings of discrimination within the work environment (Erden & Okten, 2019), social classes, and separations (Grasmick et al, 1983). In this context, our reasoning is represented in the following hypothesis:…”
Section: Paternalistic Leadership and Xenophobiamentioning
confidence: 99%
“…Thus, xenophobic behaviours may occur as a result of hierarchical and family-like attributes innate in paternalistic leadership which may lead to exclusion and marginalisation of out-group or minority members. Similarly, emphasising the dark side of paternalistic leadership, researchers caution about the possibility of nepotism and racial discrimination (Erden and Ayse, 2019: Levine and Hogg, 2010).…”
Section: The Research Contextmentioning
confidence: 99%
“…Aycan, aptly explains that authoritarian leadership is about ‘people control’, whereas authoritative leadership is to do with ‘task control’. While the latter has positive effects such as enhancing self-efficacy, hope and optimism and motivating followers to work hard and attain goals (Aycan, 2006; Karakitapoğlu-Aygün et al, 2020), authoritarianism can lead to a range of negative consequences such as discrimination, corruption, nepotism and xenophobia (Erden and Ayse, 2019; Levine and Hogg, 2010; Okun et al, 2020). In this paper, we explore these issues and show how authoritarianism can be misrepresented within a paternalistic façade, making it popularly associated with more positive paternalistic attributes such as benevolence and morality.…”
Section: The Research Contextmentioning
confidence: 99%
“…As highlighted by Erden & Otken (2019) discrimination in the execution of HR practices based on preferential treatment corresponding to the appointment, delegation, assessment, rewards, training, and working conditions might result in affecting not only the employee job performance but also the organizational performance. Besides, Shoss, Witt, & Vera (2012) found that conscientiousness and organizational politics together affect adaptive performance whereas Karatepe (2013) revealed that organizational politics affect extra-role (contextual) performance as well.…”
Section: Training and Development Adaptive Performance And Contextual Performance In The Presence Of Nepotism And Favoritismmentioning
confidence: 99%